Bi-functional heterogeneous iron complexes for catalytic conversion of epoxides to cyclic carbonates and their application in the synthesis of polyurethane. Issue 6 (23rd April 2018) - Verma, Shailesh; Nazish, Mohd.; Kureshy, Rukhsana I.; Khan, Noor-ul H.
Abstract : The development of a sustainable heterogeneous catalyst for direct conversion of CO2 to value-added chemicals is of great interest. Abstract : The development of a sustainable heterogeneous catalyst for direct conversion of CO2 to value-added chemicals is of great interest. Herein, we have developed polystyrene resin supported bi-functional Fe(iii ) complexes and studied their catalytic performance towards chemical fixation of CO2 . The synthesized complexPFe-1 showed excellent catalytic activity towards aromatic/terminal aryloxy and aliphatic epoxides for achieving mono- and bis-cyclic carbonates in the absence of any co-catalysts. Higher conversion with excellent selectivity for cyclic carbonates was obtained with the catalystPFe-1 with an added advantage of catalyst recyclability. This catalytic protocol was further extended for the synthesis of linear/cross polyhydroxyurethanes with good yield in a single step via addition polymerisation between bis-cyclic carbonate and different aliphatic diamines/triamines.